Structure of modern company innovation systems - J. V. Selyavsky; A. M. Goncharov (Путеводитель предпринимателя, 2020)
In this article the current state of innovation activity development in Russia is analyzed, a classification of innovations is given, structural model of innovation management system, taking into account the implemented innovation strategy, is proposed.